Question
upstudy study bank question image url

\( f\left(\frac{a x-1}{3}\right)=2 x+3 \) ve \( f\left(\frac{1}{3}\right)=7 \)

Ask by Stewart Sandoval. in Turkey
Nov 21,2024

Upstudy AI Solution

Tutor-Verified Answer

Answer

الدالة هي \( f(x) = 6x + 5 \).

Solution

لإيجاد دالة \( f(x) \) من المعادلة المعطاة \( f\left(\frac{a x-1}{3}\right)=2 x+3 \) والمعلومة \( f\left(\frac{1}{3}\right)=7 \)، يمكننا اتباع الخطوات التالية: 1. **إيجاد قيمة \( a \)**: نبدأ بتعويض \( x \) بقيمة معينة لنجد \( a \). لنأخذ \( x = 0 \): \[ f\left(\frac{a \cdot 0 - 1}{3}\right) = f\left(-\frac{1}{3}\right) = 2 \cdot 0 + 3 = 3 \] لذا، لدينا: \[ f\left(-\frac{1}{3}\right) = 3 \] 2. **إيجاد قيمة \( x \) بحيث \( \frac{a x - 1}{3} = \frac{1}{3} \)**: نحل المعادلة: \[ \frac{a x - 1}{3} = \frac{1}{3} \] نضرب في 3: \[ a x - 1 = 1 \] \[ a x = 2 \quad \Rightarrow \quad x = \frac{2}{a} \] 3. **تعويض \( x = \frac{2}{a} \) في المعادلة الأصلية**: \[ f\left(\frac{1}{3}\right) = 2 \cdot \frac{2}{a} + 3 \] نعلم أن \( f\left(\frac{1}{3}\right) = 7 \): \[ 7 = \frac{4}{a} + 3 \] نطرح 3 من كلا الجانبين: \[ 4 = \frac{4}{a} \] نضرب في \( a \): \[ 4a = 4 \quad \Rightarrow \quad a = 1 \] 4. **إيجاد دالة \( f(x) \)**: الآن بعد أن وجدنا \( a = 1 \)، نعود إلى المعادلة الأصلية: \[ f\left(\frac{x - 1}{3}\right) = 2x + 3 \] لنحسب \( f(x) \) عن طريق تعويض \( y = \frac{x - 1}{3} \) مما يعني \( x = 3y + 1 \): \[ f(y) = 2(3y + 1) + 3 = 6y + 2 + 3 = 6y + 5 \] لذا: \[ f(x) = 6x + 5 \] 5. **التحقق**: نتحقق من \( f\left(\frac{1}{3}\right) \): \[ f\left(\frac{1}{3}\right) = 6 \cdot \frac{1}{3} + 5 = 2 + 5 = 7 \] وهذا يتطابق مع المعطى. إذن، الدالة هي: \[ f(x) = 6x + 5 \]

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

Let's dive into the world of function transformations with a twist! The function \( f \) gives us the value \( 7 \) when we plug in \( \frac{1}{3} \). This means that if we look at this transformation \( \frac{a x-1}{3} \), we can find a connection between \( a \) and \( x \) where the output lands us back to the original function value. To solve for \( a \), let's start with rearranging this expression. If we set \( \frac{a x - 1}{3} = \frac{1}{3} \), it follows that \( ax - 1 = 1 \) or \( ax = 2 \). So, when \( x = \frac{2}{a} \), we insert this back into our original function equation and verify if \( f\left(1\right)=2*\frac{2}{a}+3 \) leads us toward a consistent \( f \) value. Now that's some mathematical magic!

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy